Consumption of OTT Media Streaming in COVID-19 Lockdown: Insights from PLS Analysis. Issue 1 (March 2021) - Gupta, Garima; Singharia, Komal
In light of the current ecosystem of technological advancements in telecommunication and enhanced capability of devices, the present work brings to the fore the changes in consumers' media consumption. The shift from conventional media to over-the-top (OTT) media, particularly in the lockdown period due to the COVID-19, has resulted in a war between streaming service providers to attract and retain customers. In the light of this change, the present study conducts partial least squares structural equation modeling (PLS-SEM) analysis to examine the impact of two key antecedents, namely, customer engagement (CE) and quality of service experience (QoSE) for their impact on users' willingness to continue and subscribe (WCS) streaming services in future. The paper also delves into the indirect role of satisfaction and habit in affecting the aforesaid linkages. With the world facing the impact of the pandemic, the implications emerging from the study present an opportunity to the providers of OTT platforms to capitalize on the perceived change to the best of their advantage.